2003
DOI: 10.1104/pp.014118
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis Phytochelatin Synthase Paradoxically Leads to Hypersensitivity to Cadmium Stress

Abstract: Phytochelatin (PC) plays an important role in heavy metal detoxification in plants and other living organisms. Therefore, we overexpressed an Arabidopsis PC synthase (AtPCS1) in transgenic Arabidopsis with the goal of increasing PC synthesis, metal accumulation, and metal tolerance in these plants. Transgenic Arabidopsis plants were selected, designated pcs lines, and analyzed for tolerance to cadmium (Cd). Transgenic pcs lines showed 12-to 25-fold higher accumulation of AtPCS1 mRNA, and production of PCs incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
177
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(197 citation statements)
references
References 42 publications
16
177
2
2
Order By: Relevance
“…Another new viewpoint towards phytoremediation is that adequate attention must be paid to the development of crop hyperaccumulators, termed by the author as "cropaccumulators", such as wheat, maize and rice [30][31][32][33]. In other words, investigations of other "noncropaccumulators" species would be of little significance in application.…”
Section: The Development Of Crop Hyperaccumulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new viewpoint towards phytoremediation is that adequate attention must be paid to the development of crop hyperaccumulators, termed by the author as "cropaccumulators", such as wheat, maize and rice [30][31][32][33]. In other words, investigations of other "noncropaccumulators" species would be of little significance in application.…”
Section: The Development Of Crop Hyperaccumulatorsmentioning
confidence: 99%
“…Studies on this field are increasing and its mechanism is more and more clear [33][34][35][36][37][38][39][40][41]. Using transgenic technology is a tendency in the future to create an ideal species purposely.…”
Section: Perspectivementioning
confidence: 99%
“…In addition, a lot of key genes have been shown to be involved in Cd detoxification and tolerance in plants. These include ZNT1, OsHMA9, OsNRAMP5, ZntA, CAD2, AtPDR12, AtPDR8, AtATM3, ACBP1, Nramp5, EIN2, and MAN3 (Pence et al, 2000;Sharma et al, 2000;Shiraishi et al, 2000;Lee et al, 2003Lee et al, , 2007Kim et al, 2006Kim et al, , 2007Xiao et al, 2008;Cao et al, 2009;Lin and Aarts, 2012;Sasaki et al, 2012;Ishikawa et al, 2012;Chen et al, 2015). It was also found that Heat shock transcription factor A4a (HsfA4a) confers Cd tolerance by up-regulating MT gene expression in wheat (Triticum aestivum) and rice (Oryza sativa; Shim et al, 2009).…”
mentioning
confidence: 95%
“…An important pathway of heavy metal detoxification in plants is the GSH-dependent PC synthesis pathway that confers plants to tolerable Cd accumulation (Grill et al, 1989;Li et al, 1997;Noctor et al, 2002;Lee et al, 2003;Kim et al, 2006;Verbruggen et al, 2009aVerbruggen et al, , 2009b. Therefore, we analyzed the growth of wild-type and ZAT6-OE plants in 1/2 MS media containing buthionine sulfoximine (BSO), an inhibitor of GSH synthesis (Kim et al, 2006).…”
Section: Zat6 Positively Regulates CD Tolerance Through the Gshdependmentioning
confidence: 99%
See 1 more Smart Citation